Draft Annual Plan 1971-72 Union Territory of Chandigarh - Planning Commission (Planning Commission, 1971)
The Poultry Project, Chandigarh was set up by the composite Punjab State during 3rd Plan on the advice of the Government of India, primarily to meet the increasing demand of eggs and poultry meat for the Military base hospitals and it aims at making an integrated approach towards the supply of quality chicks to Poultry Fanners and the undertaking marketing of poultry birds after processing them for frozen meat. For this purpose, the USAID have supplied the Project with a most modern Chicken Dressing Plant costing about £99000 (Rs.7.50 lakhs in Indian Currency). the building and the cold storage for the Plant are complete and the Plant has been put into operation, This plant has a capacity to dress, pack and freeze 5000 birds per eight hour-shift.
Union Territory of Chandigarh